MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SD MELALUI MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENTS HAVE DAN FISHBOWL - Adam, Debby Tanti; Tauran, Sonya Fanny (LPPM Universitas Advent Indonesia, 2019)
Abstract: Mathematical communication is the ability of students to explain mathematical ideas both verbally and writing. But students' mathematical communication skills are still very low compared to other countries. The purpose of this research was to find out whether there were an increase in mathematical communication skills of students who obtained the cooperative learning model Question Students Have or Fishbowl type, and the students' responses to the learning model. The sample in this research were students of VA and VC, SD KARTIKA X-3 Parongpong, West Bandung. The instrument used is a mathematical communication skills test in the form of subjective questions related to the material